Ethics Acculturation of International Counseling Students - Li, Dan; Ai, Yang (Journal of International Students, 2020)
Counseling ethics is a complex discipline; it is more than the acquisition of ethical principles, codes of ethics, and standards of practice. To disentangle the intricacies of ethics education, we use the acculturation model to conceptualize students’ learning of counseling ethics, particularly international students who experience acculturation in the general sense and the acculturation of ethics in the counseling profession specifically. A case study is presented to illustrate the four acculturation strategies that students may adopt in ethical decision-making. Implications for counselor education, practice, and research are provided.